2014
DOI: 10.1146/annurev-immunol-032713-120145
|View full text |Cite
|
Sign up to set email alerts
|

Chemokines and Chemokine Receptors: Positioning Cells for Host Defense and Immunity

Abstract: Chemokines are chemotactic cytokines that control the migratory patterns and positioning of all immune cells. Although chemokines were initially appreciated as important mediators of acute inflammation, we now know that this complex system of approximately 50 endogenous chemokine ligands and 20 G protein-coupled seven-transmembrane signaling receptors is also critical for the generation of primary and secondary adaptive cellular and humoral immune responses. Recent studies demonstrate important roles for the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
1,598
1
18

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,662 publications
(1,653 citation statements)
references
References 261 publications
(234 reference statements)
36
1,598
1
18
Order By: Relevance
“…1). We found that TILs generally expressed an activated chemokine receptor pattern 17 including high frequencies of CCR5 + , CXCR3 + and CXCR4 + (Fig. 1C).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…1). We found that TILs generally expressed an activated chemokine receptor pattern 17 including high frequencies of CCR5 + , CXCR3 + and CXCR4 + (Fig. 1C).…”
Section: Resultsmentioning
confidence: 85%
“…While IL-8 may induce recruitment of T cells, T cells' extravasation and migration into peripheral tissues rely on selectin and integrin binding in concert with chemokine signaling to mediate rolling and firm adhesion to the endothelial wall. 17 , 36 Our xenograft model relies on stromal chemokines secreted by mouse endothelial cells and fibroblasts, and despite some sequence similarity and evolutionary conserved regions, there is a greater disparity, and these may not necessarily support T cell adhesion, extravasation and tumor infiltration. 37 In line with this, HEVs in human melanoma lesions have been shown to be major gateways for tumor infiltrating lymphocytes, 38 however lack of host immune cells in the NOG mouse model, and thus no orchestrating chemokines and cytokines, HEVs are most likely not produced in this model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Expression profiling revealed that the chemotaxis pathway was more active in FoxD1 þ /Col1 À pericytes than in other lung fibroblasts, including higher levels of Ccl4 (macrophage inflammatory protein-1b), Cxcl2 (macrophage inflammatory protein-2), Ccl21 (secondary lymphoid-tissue chemokine), and Ccl5 (regulated on activation normal T cell expressed and secreted), which combined could attract neutrophils, monocytes, macrophages, dendritic cells, NK cells, and other classes of innate lymphocytes, and T cells (Figure 3). 10,63 The Col1 À pericyte subset also preferentially expressed a variety of immune sensing and response genes. Activation of the NLRP3 inflammasome to produce IL-1b is one of the strongest defenses against infections, but can also severely damage tissue and plays a highly pathogenic role in lung fibrosis.…”
Section: Pericytes Act As the Immune System's Sentriesmentioning
confidence: 99%
“…In contrast to conventional T cells that recirculate between SLOs via blood and lymph, Tregs exhibit an expanded migratory pattern that includes tertiary tissues (14). A previous report demonstrated that KLF2 maintains naive T cells in a homeostatic migration pattern and, much like activated lymphocytes that quickly degrade this transcription factor, Klf2 excision causes quiescent T cells to vacate SLOs and enter peripheral tissues (15).…”
Section: Klf2 Acts As a Rheostat To Control Expression Of Treg Homingmentioning
confidence: 99%